ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารสถาบันอุดมศึกษาไทยในเขตภาคตะวันออก - กมลรุ่งเรือง, ธิดา (วารสารการบริหารปกครอง มหาวิทยาลัยกาฬสินธุ์, 2025)
การศึกษาเรื่อง ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารสถาบันอุดมศึกษาไทย ในเขตภาคตะวันออก มีวัตถุประสงค์เพื่อศึกษาปัจจัยด้านสมรรถนะ ตลอดจนปัญหา และอุปสรรคของผู้บริหารที่ส่งผลต่อภาวะผู้นำการเปลี่ยนแปลงของผู้บริหาร วิธีดำเนินการวิจัยใช้รูปแบบวิธีวิจัยเชิงผสม โดยวิธีวิจัยเชิงคุณภาพและเชิงปริมาณ กลุ่มตัวอย่างในการศึกษา ได้แก่ การสัมภาษณ์แบบเจาะลึกจากผู้บริหาร สถาบันอุดมศึกษาไทยในเขตภาคตะวันออก และวิเคราะห์ข้อมูลแบบสอบถามจาก บุคลากรที่ปฏิบัติงานที่เกี่ยวข้องกับสำนักงานอธิการบดีภายในสถาบันอุดมศึกษาไทย ในเขตภาคตะวันออกผลการศึกษาพบว่า ระดับความคิดเห็นของบุคลากรที่ปฏิบัติงาน ที่มีต่อสมรรถนะของผู้บริหาร 13 ตัวชี้วัด อยู่ในระดับส่งผลมาก โดยตัวชี้วัดที่ได้รับ คะแนนมากที่สุดคือ ด้านสมรรถนะในการมองภาพรวม และพบว่า คุณลักษณะ 4 ประการ ของภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารในภาพรวมอยู่ในระดับมาก โดย ตัวชี้วัดที่ได้รับคะแนนมากที่สุดคือ ด้านการสร้างแรงบันดาลใจ และพบว่าปัญหาและ อุปสรรคทางด้านสมรรถนะของผู้บริหารที่ส่งผลต่อภาวะผู้นำการเปลี่ยนแปลงของ ผู้บริหารส่วนใหญ่ให้ความเห็นว่า สิ่งสำคัญ คือ การที่ผู้บริหารมีความจำเป็นต้องดูแล สุขภาพของตนเอง เพราะสุขภาพของผู้บริหารถือได้ว่าเป็นปัญหาและอุปสรรคทั้ง ทางตรงและทางอ้อมต่อความท้าทายในการบริหารงาน This research aimed to study: 1) factors of the competency that affecting to transformational leadership of the administrators of Thai higher education in eastern region of Thailand.; 2) administrators transformational leadership of Thai higher education in eastern region of Thailand. ; 3) problems and obstacles to administrators competency affect their transformational leadership of Thai higher education in eastern region of Thailand, using a mixed method both quantitative and qualitative research. The nonprobability samplings were 6 of Thai higher education administrators in eastern region of Thailand and personnel served in the university president’s office in eastern region of Thailand. The research findings suggested: 1) administrators competency of Thai higher education consists of13types have the overall level was at a high level. The measure received the most votes are analyzing and deciding. 2) The administrators transformational leadership of Thai higher education consists of 4 types have the overall level was at a high level. The indicators of the highest marks were motivation. and 4) study the problems and obstacles encountered by factors of the competency that affecting to transformational leadership of the administrators of Thai higher education in eastern region of Thailand, Most administrators of Thai higher education commented; One thing that was important was not defined in detail in the competency of the managerial was necessary to take care of their health. Because of health management can be considered as barriers to the challenge for the administration. Poor health would result in both direct and indirect administration, certainly.